2005
DOI: 10.1093/ps/84.2.328
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and thermal characteristics of Thai indigenous and broiler chicken muscles

Abstract: The microstructure and thermal characteristics of Thai indigenous (Gallus domesticus) and broiler chicken (commercial line CP707) biceps femoris and pectoralis muscles were determined. Perimysium thicknesses were 14.2 microm for biceps femoris muscle and 7.10 microm for pectoralis muscle of indigenous chicken muscles, thicker than those of broiler muscles, which were 9.93 microm for biceps femoris muscle and 3.87 microm for pectoralis muscle (P < 0.05). Five endothermic peaks with peak transition temperatures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 24 publications
8
46
1
Order By: Relevance
“…The swelling of fish muscle fiber can be clearly seen when comparing Fig. 6A, C and E. The average diameter of white fibers in raw chicken muscle has been reported from 32.6 to 68.2 mm (Wattanachant et al, 2005a).…”
Section: Microscopy Examinationmentioning
confidence: 75%
“…The swelling of fish muscle fiber can be clearly seen when comparing Fig. 6A, C and E. The average diameter of white fibers in raw chicken muscle has been reported from 32.6 to 68.2 mm (Wattanachant et al, 2005a).…”
Section: Microscopy Examinationmentioning
confidence: 75%
“…Ono et al, (1993) and Muthukumar et al, (2011) reported significant increase (41.51 m to 58.24 m) in MFD with age in broilers. Wattanachant et al, (2005) reported the fiber diameter of Thai indigenous chicken at age 16 weeks in thigh muscle (31.1 m) was higher than breast muscle (28.9 m) and in contrary they observed opposite results in broilers i.e. thigh muscle (20.4 m) MFD was lower than breast muscle (26.6 m) and differences in muscle fiber diameter was attributed to the differences in age, rate of rigor onset, and degree of sarcomere shortening as suggested by Smith and Fletcher (1988).…”
Section: Resultsmentioning
confidence: 99%
“…The development of connective tissue and thickness of collagen fibrils was slower in chickens than in many other fast growing species (Shiba et al, 2006;Fernandez et al, 2001). The perimysium of indigenous chicken muscles was thicker than in broilers, which led to an extremely tough meat (Wattanachant et al, 2005). However, the increasing of endomysium and perimysium thickness was paralleled by a significant increase in muscle fibre diameter (Lachowicz et al, 2007;Wojtysiak, 2013).…”
Section: Traitsmentioning
confidence: 99%